2020
DOI: 10.1159/000512100
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Ammonia Clearance for Hyperammonemia in Critically Ill Patients: A Scoping Review

Abstract: <b><i>Introduction:</i></b> Hyperammonemia is a life-threatening condition. However, clearance of ammonia via extracorporeal treatment has not been systematically evaluated. <b><i>Methods:</i></b> We searched EMBASE and MEDLINE databases. We included all publications reporting ammonia clearance by extracorporeal treatment in adult and pediatric patients with clearance estimated by direct dialysate ammonia measurement or calculated by formula. Two reviewers screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…We would expect to observe an improvement in mortality rate due to a reduction in complications from accumulated toxins caused by liver dysfunction. Consistent with this, several clinical studies have reported that CRRT can reduce serum bilirubin and ammonia levels [ 29 , 30 ]. However, literature regarding the relationship between bilirubin, ammonia excretion, and mortality is sparse.…”
Section: Discussionsupporting
confidence: 72%
“…We would expect to observe an improvement in mortality rate due to a reduction in complications from accumulated toxins caused by liver dysfunction. Consistent with this, several clinical studies have reported that CRRT can reduce serum bilirubin and ammonia levels [ 29 , 30 ]. However, literature regarding the relationship between bilirubin, ammonia excretion, and mortality is sparse.…”
Section: Discussionsupporting
confidence: 72%
“…Acute kidney injury requiring CRRT is a common manifestation of MOF in both ALF and ACLF[ 83 - 85 ]. In addition, CRRT is commonly utilized in patients with severe hyperammonemia to reduce the risk of ICH and cerebral edema[ 49 , 50 , 86 ]. CRRT is usually delivered over 24 h and the interruption of CRRT for TPE may compromise the duration of CRRT.…”
Section: Combination With Other Extracorporeal Therapymentioning
confidence: 99%
“…Ammonia clearance in these studies varied considerably, often implausibly. However, higher blood and dialysate flow rates were consistently correlated with greater ammonia clearance, i.e., higher effluent rate and dose appeared to increase clearance [18]. Accordingly, we did not find any difference in clearance comparing CRRT techniques, where the dose by effluent rate per hour was the same.…”
Section: Discussionmentioning
confidence: 64%
“…To our knowledge, this is the first study to directly compare ammonia clearance between different CRRT techniques. There are limited studies investigating the extracorporeal clearance of ammonia in the critically ill. A recent review found only 13 published papers on this topic [18]. The largest body of research to date has occurred in the paediatric field, where both intermittent haemodialysis and CRRT have been used successfully to treat hyperammonaemia [19][20][21].…”
Section: Relationship To Previous Studiesmentioning
confidence: 99%